2015
DOI: 10.1016/j.rbr.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Coexistência de lúpus eritematoso sistêmico e doença falciforme: relato de caso e revisão da literatura

Abstract: SLE and SCD are chronic diseases that have several clinical and laboratory findings in common, meaning difficult diagnosis and difficulty in finding the correct treatment. Although the association between these diseases is not common, it is described in literature, so it is imperative that physicians who treat such diseases be alert to this possibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Robazzi et al [5] in 2012, counted 45 cases of association between sickle cell disease to lupus. Other studies [6] [7] [8] [9] [10] also showed this association in the literature with 56 cases as of July 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Robazzi et al [5] in 2012, counted 45 cases of association between sickle cell disease to lupus. Other studies [6] [7] [8] [9] [10] also showed this association in the literature with 56 cases as of July 2017.…”
Section: Discussionmentioning
confidence: 99%